Influence Of Religiosity, Perception Of Entrepreneurship, And Locus Of Control On Entrepreneurial Decisions - Indi Mardalena; Supardi Mursalin; Yetti Afrida Indra (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: The purpose of this study is to determine the influence of religiosity, entrepreneurial perception, and locus of control on entrepreneurial decision-making. To examine this, the researcher employed a quantitative method with primary data collection through questionnaires distributed to 70 respondents. The data were analyzed using multiple linear regression with SPSS version 25. The results indicate that the religiosity variable has a positive and significant effect on entrepreneurial decision-making, the entrepreneurial perception variable has a positive and significant effect on entrepreneurial decision-making, while the locus of control variable has a positive but not significant effect on entrepreneurial decision-making. Simultaneously, the three variables have a significant effect on entrepreneurial decision-making.